Effect of pulsed electric field on the number and cell membrane of Vibrio parahaemolyticus in salted squid: Pengaruh medan listrik berdenyut terhadap jumlah total dan membran sel Vibrio parahaemolyticus pada cumi asin - Darmawan, Arry; Kusumaningrum, Harsi Dewantari; Wulandari, Nur; Nurjanah, Siti; Sugiarto, Anto Tri (Jurnal Pengolahan Hasil Perikanan Indonesia, 2025)
Squid are susceptible to bacterial contamination by Vibrio parahaemolyticus, with a prevalence of 80%. Squid preservation is generally achieved by drying after brine salting, which does not always completely stop the growth of V. parahaemolyticus. To reduce bacterial numbers, a boiling process is usually conducted before drying. This study aimed to determine the optimal electric field and duration for inactivating V. parahaemolyticus and evaluating the effectiveness of pulsed electric fields (PEF) technology on salted squid. PEF technology specifications with a current strength of 2 amperes using electric fields (3.5, 7, and 10.5 kV/cm) and time durations (10, 20, and 30 s). Bacterial reduction by electric fields was observed using colony counts, followed by counting of dead cells using a flow cytometer. Bacterial damage was observed using a scanning electron microscope. The results showed that PEF with the highest intensity (10.5 kV/cm for 30 s) reduced V. parahaemolyticus by 66.12% at high contamination levels (approximately 106 CFU/g) and 97.63% at low contamination levels (approximately 102 CFU/g) in salted squid. These results were comparable to those obtained after boiling treatment (2 min, 85°C). Damage to the bacterial cell membrane increased due to the increasing electric field, as observed by increasing in red fluorescing cells by flow cytometry and cell damage by SEM. PEF is a promising alternative technology for producing salted squid.